A Systematic Review of Health Informatics Applications in Clinical Practice and Healthcare Management - Javeedullah, Mohammed; Zeb, Shah (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Healthcare is improved in both healthcare delivery and administrative =tasks by integrating technology and data management through health informatics. This analysis looks at how some health informatics systems are used, for example, Electronic Health Records (EHRs), Clinical Decision Support Systems (CDSS), Health Information Exchanges (HIE) and telemedicine platforms. As a result of these technologies, patient safety has improved, quality of care has risen and daily work is more efficient due to updated data, streamlined procedures and evidence being easily used. Issues related to making different systems work together, safeguarding private information and being reluctant to change keep many from using AI widely. It also looks at new technologies like artificial intelligence, block chain and telehealth which could make healthcare better. Overcoming these issues and using these new methods gives health informatics the ability to make healthcare more efficient, personalized and sustainable worldwide.